ANALISIS KESULITAN SISWA DALAM MENEMUKAN GAGASAN POKOK PADA TEMA CUACA SUBTEMA PENGARUH CUACA BAGI KEHIDUPAN MANUSIA PADA SISWA KELAS III SEKOLAH DASAR - Ade Kalpika Budiningtyas (Universitas Muria Kudus, 2022)
Reading skills are very important for students because the center of learning is reading. Various subjects and information that can be known and mastered by students through reading activities. When entering elementary school age, children are taught to read and write. In this case, children are required to improve their reading skills to obtain information. The purpose of this study was to find out the difficulties experienced by students in the Indonesian language subject in finding main ideas on the weather theme, the sub-theme of the influence of weather on human life in third grade elementary school, describing solutions to overcome difficulties in finding main ideas. The type of research used is a qualitative research type, with a case study research design. The subjects of this study were the third grade students of SD 2 Ngembal Kulon, totaling 15 people. In this study data collection using test methods, documentation, interviews, observation. Data analysis techniques from data reduction, data presentation, and drawing conclusions. The results showed that the causes of difficulty in finding the main idea were not understanding the meaning of the main idea, vocabulary that did not know its meaning and sentences were too long. Based on the results of the research and several other relevant studies, the solution to overcome the difficulty of finding the main idea of paragraphs for third grade students of SD 2 Ngembal Kulon is that teachers can optimize the use of media that can attract students' attention and change the use of methods or learning models that have been used so far to be more varied.